Sinonímias e descrições em Adetus LeConte (Coleoptera, Cerambycidae, Lamiinae, Apomecynini) - Martins,Ubirajara R. (2003)
Based on the photographs (color slides) taken from the type specimens of Adetus species, the following synonyms are established: Adetus subcostatus Aurivillius, 1900 = A. auratoides Breuning, 1943 syn. nov.; A. leucostigma Bates, 1880 = A. venezuelensis Breuning, 1942 syn. nov.; A. pulchellus (Thomson, 1868) = A. laterialbus Breuning, 1942 syn. nov.; A. irregularis (Breuning,1939) = A. gracilis Breuning, 1940 syn. nov.; A. flavescens Melzer, 1934 = A. strandi Breuning, 1940 syn. nov. = A. mediofasciculatus Breuning, 1943 syn. nov.; A. modestus Melzer, 1934 = Atimuropsis densepunctata Breuning, 1939 syn. nov. New species described: Adetus multifasciatus sp. nov. (Brazil, São Paulo); A. lineatus sp. nov. (Brazil, Distrito Federal); A. linsleyi sp. nov. (Ecuador, Los Ríos); A. pacaruaia sp. nov. (Peru, Huanuco), and A. pinima sp. nov. (Peru, Junin). Adetus marmoratus Breuning, 1942 is redescribed.